DAMPAK KEIKUTSERTAAN FUN RUN TERHADAP TINGKAT KEBUGARAN JASMANI PELAJAR - Bagus Kuncoro; Pipit Fitria Yulianto; Muhammad Ilham Dewanto; Nico Ponco Sulistyo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this research is to investigate the differences in physical fitness levels between students who participate in fun run activities and those who do not. A comparative quantitative method with a cross-sectional design was used in this study. The research sample consists of 60 students from the sixth grade of SDN Sondakan Surakarta. They were divided into two groups: 30 students who participated in the fun run and 30 students who did not participate in the fun run. The 12-minute run test, push-ups, sit-ups, and shuttle run were used to measure the fitness levels of each group. The results were analysed using an independent sample t-test and descriptive statistics. The research results show that in every aspect measured, the fun run participant group is more fit compared to the non-participant group. Cardiorespiratory endurance, arm muscle strength, abdominal muscle endurance, and agility were all significantly different (p < 0.05). Fun run participants also had higher weekly physical activity levels and were more motivated to exercise. The results show that fun runs are one type of physical activity that helps elementary school students become more active and healthier. Therefore, fun running should be included in the PJOK education program and the Healthy School Movement.